2004
DOI: 10.1007/s10545-005-0069-y
|View full text |Cite
|
Sign up to set email alerts
|

Heparan sulfate levels in mucopolysaccharidoses and mucolipidoses

Abstract: Glycosaminoglycans are accumulated in both mucopolysaccharidoses (MPS) and mucolipidoses (ML). MPS I, II, III and VII and ML II and ML III patients cannot properly degrade heparan sulphate (HS). In spite of the importance of HS storage in the metabolic pathway in these diseases, blood and urine HS levels have not been determined systematically using a simple and economical method. Using a new ELISA method using anti-HS antibodies, HS concentrations in blood and urine were determined in MPS and ML II and ML III… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
59
2
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(70 citation statements)
references
References 22 publications
8
59
2
1
Order By: Relevance
“…Additional data from more patients with MPS VII will be required to validate these biomarkers. Blood KS level in control subjects were high during the first 5 years of life and then steadily declined with age before stabilizing in late teenage years, in agreement with prior studies (Tomatsu et al 2005a;Thonar et al 1988). The level of blood KS in patients with MPS IVA was significantly higher than age-matched controls in older children and adults.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Additional data from more patients with MPS VII will be required to validate these biomarkers. Blood KS level in control subjects were high during the first 5 years of life and then steadily declined with age before stabilizing in late teenage years, in agreement with prior studies (Tomatsu et al 2005a;Thonar et al 1988). The level of blood KS in patients with MPS IVA was significantly higher than age-matched controls in older children and adults.…”
Section: Discussionsupporting
confidence: 90%
“…The decreased level of KS in the blood as healthy teenagers move towards adulthood is consistent with the fact that their growth rate begins to decline during this period. In previous studies we showed that blood KS level in severely affected MPS IVA patients less than 10 years old is markedly elevated and that KS level declines to near-normal or normal levels after 15 year of age, following closing of growth plate (Tomatsu et al 2005a(Tomatsu et al , 2010c. In the present study, KS levels are less dramatic and may reflect fewer young patients in this study and/or a cohort of patients with a less severe phenotype.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The storage materials, heparan sulfate and dermatan sulfate, accumulate within lysosomes and are present in plasma, urine, and cerebral spinal fluid (Neufeld and Muenzer 2001;Tomatsu et al 2005). Although patients with MPS II appear normal at birth, the disease is progressive and signs and symptoms usually become apparent during early childhood (Wraith et al 2008).…”
Section: Introductionmentioning
confidence: 99%